Pelayanan Tenaga Administrasi Sekolah Urusan Kepegawaian Berbasis Teknologi Informasi Pada SMK se-Kota Padang - Diah Rahayu; Rusdinal Rusdinal; Nelfia Adi; Hanif Al Kadri (Journal of Educational Administration and Leadership, 2021)
This study intends to determine the service of school administration personnel for information technology-based personnel at SMK in Padang City. This type of research is descriptive quantitative, collecting data using a questionnaire with a Likert scale. This study discusses the service of school administrative personnel for personnel affairs, which can be described based on indicators, namely: 1) awareness in providing services has a value of 4.4 in the good category, 2) the ability to provide services has a value of 4.42 in the good category, 3) means of providing services has a value of 4.49 in the good category. Overall, information technology-based staffing services at SMK in Padang City have a score of 4.45 in the good category.